Deviant leisure: A criminological perspective. (February 2018) - Smith, Oliver; Raymen, Thomas
This article explains why an understanding of deviant leisure is significant for criminology. Through reorienting our understanding of 'deviance' from a contravention of norms and values to encompassing engagement in behaviour and actions that contravene a moral 'duty to the other', the new 'deviant leisure' perspective outlined here describes activities that through their adherence to cultural values inscribed by consumer capitalism, have the potential to result in harm. Using the ideological primacy of consumer capitalism as a point of departure, we explore the potential for harm that lies beneath the surface of even the most embedded and culturally accepted forms of leisure. Such an explanation requires a reading that brings into focus the subjective, socially corrosive, environmental and embedded harms that arise as a result of the commodification of leisure. In this way, this article aims to act as a conceptual foundation for diverse yet coherent research into deviant leisure.